Faktor yang Memengaruhi Financial Satisfaction pada Masyarakat Kabupaten Pamekasan - Dinda Arfiana Rusdini (Jurnal Ilmu Manajemen, 2021)
The purpose of this research is to determine the influence of income, debt, and financial literacy on financial satisfaction through financial management behaviour as a mediating variable. This causality research using per capita income data from BPS shows that Pamekasan district has the lowest per capita income so that Pamekasan district as an object with a total sample of 193 respondents by offline questionnaire. Using SEM techniques and processed with AMOS tools, the conclusion is that only financial literacy influences financial management behaviour because of their high savings awareness. Income does not influence financial satisfaction because even their income is high enough, but they still have high debt. Debt does not affect financial satisfaction because having debt does not necessarily cause financial anxiety. Some respondents have debt and have financial satisfaction, but some do not. Financial literacy has no influence on financial satisfaction but influences financial management behaviour, and financial management behaviour has not been able to meditate because their saving behaviour is unable to increase their satisfaction